Factors affecting out-of-pocket expenditures for chronic and acute illnesses in Bangladesh - Jinat Jahan Khan; Farzana Sehrin; Zahidul Quayyum; Abdur Razzaque Sarker; Mohammad Shafiqur Rahman (PLoS ONE, 2025)
Background In the absence of universal healthcare protection, out-of-pocket (OOP) expenditures are the main source of healthcare financing in Bangladesh. This study assesses the disparities in the overall and the components of OOP expenditures among households with both chronic and acute illnesses compared to those having acute illnesses only. It also identifies factors influencing OOP expenditures over time and examines patterns related to various illness conditions. Materials and methods Data from the Household Income and Expenditure Surveys (HIES) of 2016–17 and 2022 were used. A Log-linear Multiple Regression Model was employed to identify factors influencing OOP expenditures in households with different disease profiles. Results The average OOP expenditures increased significantly from 2016 to 2022, even after inflation adjustments. Higher expenditures were observed in urban households BDT 939.34 in 2016 and BDT 1605.36 in 2022, and in households having both chronic and acute illness conditions with OOP expenditure of BDT 2290.43 and BDT 3525.32 in 2016 and 2022 respectively. Wealthier households spent more on healthcare, with the cost of medicines being the largest component with over 50% of total OOP expenditures. The regression analysis suggests that area of residence (urban vs rural), household size, level of education of the household head, the presence of elderly members (≥60 years), the number of employed members and sick household members, and hospitalisation of household members were mainly responsible for higher OOP expenditure. Conclusion Our study provides valuable insights on the determinants of OOP expenditures over time, with a notable increase among households managing both chronic and acute illnesses, and in urban areas. Key contributors to increased expenditures include medicines, medical tests and surgery costs, with cancer causing higher expenses. This study recommends improving treatment protocols help reduce unnecessary prescriptions of medicine and investigations, and alleviate financial burdens of the vulnerable population.